2020
DOI: 10.1177/0271678x20923857
|View full text |Cite
|
Sign up to set email alerts
|

The cellular basis of increased PET hypoxia tracer uptake in focal cerebral ischemia with comparison between [18F]FMISO and [64Cu]CuATSM

Abstract: PET hypoxia imaging can assess tissue viability in acute ischemic stroke (AIS). [18F]FMISO is an established tracer but requires substantial accumulation time, limiting its use in hyperacute AIS. [64Cu]CuATSM requires less accumulation time and has shown promise as a hypoxia tracer. We compared these tracers in a M2-occlusion model (M2CAO) with preserved collateral blood flow. Rats underwent M2CAO and [18F]FMISO ( n = 12) or [64Cu]CuATSM ( n = 6) examinations. [64Cu]CuATSM animals were also examined with MRI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Ultimately, it decreases adenosine triphosphate concentrations and causes cell death. [ 43 , 44 ] Cheng Q et al have demonstrated a positive correlation between endothelial progenitor cells (EPCs) and bone mass. [ 45 ] EPCs are capable of secreting bone morphogenetic proteins and other osteoblasts, which promote osteoblast proliferation and differentiation, thus accelerating fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, it decreases adenosine triphosphate concentrations and causes cell death. [ 43 , 44 ] Cheng Q et al have demonstrated a positive correlation between endothelial progenitor cells (EPCs) and bone mass. [ 45 ] EPCs are capable of secreting bone morphogenetic proteins and other osteoblasts, which promote osteoblast proliferation and differentiation, thus accelerating fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…Precursor (1-(2′-Nitro-1′-imidazolyl)-2- O -tetrahydropyranyl-3- O -toluenesulfonyl-propanediol, NITTP) was used from Advanced Biochemical Compounds (ABX) and the synthesis of FMISO was performed on a FASTlab synthesis module (GE Healthcare) according to the manufacturer’s instructions. The product was then sterilized by filtration through a Millex-GV 0.22 µm sterile filter (Merck Millipore) 35 .…”
Section: Methodsmentioning
confidence: 99%
“…[ 64 Cu]Cu-ATSM may have enhanced BBB penetration over [ 18 F]FAZA which is cleared from the urinary system [64,65]. [ 64 Cu]Cu-ATSM had higher uptake in the hypoxia tissues and more rapid washout in normoxic cells than [ 18 F]fluoromisonidazole ([ 18 F]FMISO), the latter requiring at least 2-h equilibrium before scanning is commenced [39,45,66]. However, Little et al found that [ 18 F] FMISO but not [ 64 Cu]Cu-ATSM or [ 64 Cu]Cu-ATSE identified hypoxic regions in acute ischemic stroke models [66], validating the negative results previously reported [67].…”
Section: Cu-atsm In Imaging Cancers and Neurodegenerative Diseasesmentioning
confidence: 99%
“…[ 64 Cu]Cu-ATSM had higher uptake in the hypoxia tissues and more rapid washout in normoxic cells than [ 18 F]fluoromisonidazole ([ 18 F]FMISO), the latter requiring at least 2-h equilibrium before scanning is commenced [39,45,66]. However, Little et al found that [ 18 F] FMISO but not [ 64 Cu]Cu-ATSM or [ 64 Cu]Cu-ATSE identified hypoxic regions in acute ischemic stroke models [66], validating the negative results previously reported [67]. So far, nitroimidazole-derived tracers, such as [ 18 F]FMISO and the sugar-coupled tracer [ 18 F]FAZA, are still the prime contenders in imaging hypoxia [68].…”
Section: Cu-atsm In Imaging Cancers and Neurodegenerative Diseasesmentioning
confidence: 99%